A Novel Interventional Guidance Framework for Transseptal Puncture in Left Atrial Interventions - Pedro Morais (2018)
Access to the left atrium is required for several percutaneous cardiac interventions. In these procedures, the inter-atrial septal wall is punctured using a catheter inserted in the right atrium under image guidance. Although this approach (transseptal puncture - TSP) is performed daily, complications are common. In this work, we present a novel concept for the development of an interventional guidance framework for TSP. The pre-procedural planning stage is fused with 3D intra-procedural images (echocardiography) using manually defined landmarks, transferring the relevant anatomical landmarks to the interventional space and enhancing the echocardiographic images. In addition, electromagnetic sensors are attached to the surgical instruments, tracking and including them in the enhanced intra-procedural world. Two atrial phantom models were used to evaluate this framework. To assess its accuracy, a metallic landmark was positioned in the punctured location and compared with the ideal one. The intervention was possible in both models, but in one case positioning of the landmark failed. An error of approximately of 6 mm was registered for the successful case. Technical characteristics of the framework showed an acceptable performance (frame rate ~5 frames/s). This study presented a proof-of-concept for an interventional guidance framework for TSP. However, a more automated solution and further studies are required. (c) Springer Nature Switzerland AG 2018.